Information as a Cultural Formation - Abril, Gonzalo (CIC. Cuadernos de Información y Comunicación, 2007)
Against the today’ s imprecision about the meaning of the term “information”, this article proposes a cultural interpretation of informative processes and facts: the information means the primary importance of the communicability conditions, as well as the functional and modular fragmentation of texts, and also its adaptation to formats psycho-technically oriented to the control of the receiving activity. The historical development of information as a “cultural formation” is due in great part to the technical circumstances, to the forms of knowledge and to the visual culture, which were born from the printing press, as well as to the demands of homologation and reproduction implicated in the development of capitalism.